Pelatihan Fundamental Pemrograman Java di Sekolah Vokasi Jurusan RPL (Rekayasa Perangkat Lunak) Melalui Program Kelas Industri - Mudafiq Riyan Pratama; Afrizal Himawan; Anisa Istiqomah; Gamasiano Alfiansyah; Selvia Juwita Swari (Puslitbang Sinergis Asa Professional, 2022)
Programming is not just making a computer program, it can even create and control a computer according to the wishes of the maker. In its manufacture requires a certain language, one of which is the Java programming language. To become a reliable programmer, it should be learned first is about programming fundamentals. The goal is to learn programming fundamentals so that prospective programmers have a strong foundation in building a complex program. The major in vocational schools that study programming is the RPL (Software Engineering) major. To produce graduates who are skilled in programming, what must be taught first is the fundamentals of programming. So in class X, vocational school students are taught the fundamentals of programming with the Java programming language. In its implementation, this community service activity is divided into 4 stages, namely preliminary (field studies and signing of cooperation agreements), preparation of materials, training and quizzes, and evaluation. This training activity uses problem-based learning and project-based learning methods so that students are accustomed to solving problems that occur in the form of computer program projects. Training activities are carried out online through Zoom Meetings, while offline training is carried out at schools during visits at the beginning, middle, and end of the semester. In addition, there are also groups via Telegram as a medium for giving quizzes and discussions. Quiz is made in several models, namely in the form of multiple-choice, guess the output of program code, puzzles, and case studies that must be solved by programming. Each activity is given assessment points, namely online presence, offline activity, quiz answers, completion of challenges, and test scores.